2023
DOI: 10.1017/wsc.2023.20
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature and heat units on zoysiagrass response to herbicides during post-dormancy transition

Abstract: In the transition zone, turfgrass managers generally utilize dormancy period of warm-season turfgrass to apply herbicides for managing winter annual weeds. Although this weed control strategy is common in bermudagrass, it has been less adopted in zoysiagrass (Zoysia spp.) due to variable turfgrass injury during post-dormancy transition. Previous research reported that air temperature could affect weed control and crop safety from herbicides. Growth chamber studies were conducted to evaluate zoysiagrass respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Zoysiagrass response to glyphosate is generally acceptable when turf is treated not later than 200 GDD 5C . Craft et al (2023) demonstrated that the magnitude of herbicide injury on zoysiagrass after glyphosate application is temperature dependent, while glufosinate-injured turfgrass, regardless of temperature prevalent during application timing. Three times more glufosinate absorbed into zoysiagrass leaves compared to glyphosate and both herbicides absorbed more readily into stolons compared to leaves (Craft 2021).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Zoysiagrass response to glyphosate is generally acceptable when turf is treated not later than 200 GDD 5C . Craft et al (2023) demonstrated that the magnitude of herbicide injury on zoysiagrass after glyphosate application is temperature dependent, while glufosinate-injured turfgrass, regardless of temperature prevalent during application timing. Three times more glufosinate absorbed into zoysiagrass leaves compared to glyphosate and both herbicides absorbed more readily into stolons compared to leaves (Craft 2021).…”
Section: Resultsmentioning
confidence: 98%
“…However, when zoysiagrass was mown at 6.5 cm at the other four site years, zoysiagrass had 91 green leaves dm −2 (Figure 2). Previous research conducted in Blacksburg, VA, on turf mown within the same height ranges indicates that the 237 green leaves dm −2 at 1.9 cm height of cut (HOC) would result in 39% green turf, and the 91 green leaves at 6.5 cm HOC would result in 20% green turf cover of zoysiagrass (Craft et al 2023). These estimates agree with the actual observed green cover at 350 GDD 5C , which averaged 49% and 18% over the 4 site years each for turf maintained at 1.8 and 6.5 cm, respectively (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation